Filsafat Hukum Islam : Implikasi Logis terhadap Konstruksi Pendidikan Islam - Mukhammad Ilyasin (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2012)
For a long time, Islamic law have wrestled with reality, and its proved that methodology of Islamic law is always suitable with anything era. Of course, it is caused by role of philosophy Islamic law in which there are two methodology, that is falsafah al-tasyri' and falsafah al-syari'ah. From both of them, we can know any wisdom about enacted the law (hikmah al-tasyri) and intention of law and the secret of law (asrar al-ahkam). With such paradigm, construction of Islamic education theory must be suitable with era growth and hoped in line with both of the Islamic law analysis. As a result, Islamic education theory can be able to growth itself according to moving era and human characteristic as a subject and also object of Islamic education.